Threehalf-turn antennas start-up - Moiseenko, V.E.; Lozin, A.V.; Kozulia, M.M.; Korovin, V.B.; Beletskii, A.A.; Baron, D.I.; Grigor’eva, L.I.; Chechkin, V.V.; Mironov, Yu.K.; Romanov, V.S.; Shapoval, A.N.; Makhov, M.M.; et al. (Вопросы атомной науки и техники, 2019)
The start-up experiments were carried out at Uragan-2M stellarator with the Three-Half-Turn antenna (THT) without any pre-ionization. Conditions for optimal gas breakdown were found out through the variation of the neutral gas pressure, magnetic field strength and anode voltage of RF generator. The plasma parameters were measured with three Langmuir probes, optical spectroscopy and mutichord optical diagnostics. На стелараторі Ураган-2М було проведено модельні експерименти зі старту трьохнапіввиткової (ТНВ) антени без предіонізації. Підбором тиску нейтрального газу, напруженості магнітного поля й анодної напруги ВЧ-генератора було знайдено оптимальні умови пробою газу. Параметри плазми вимірювались трьома ленгмюрівськими зондами, оптичною спектроскопією та багатохордовою оптичною діагностикою. На стеллараторе Ураган-2М были проведены моделирующие эксперименты по старту трёхполувитковой (ТПВ) антенны без предионизации. Подбором давления нейтрального газа, напряжённости магнитного поля и анодного напряжения ВЧ-генератора были найдены оптимальные условия пробоя газа. Параметры плазмы измерялись тремя ленгмюровскими зондами, оптической спектроскопией и многохордовой оптической диагностикой.